2012
DOI: 10.2174/187152612804142215
|View full text |Cite
|
Sign up to set email alerts
|

Chromium-Picolinate Therapy in Diabetes Care: Individual Outcomes Require New Guidelines and Navigation by Predictive Diagnostics

Abstract: Aims Nephropathy is the leading secondary complication of metabolic syndrome. Nutritional supplement by chromium-picolinate is assumed to have renoprotective effects. However, potential toxic effects reported increase concerns about safety of chromium-picolinate. The experimental design aimed at determining, whether the treatment with clinically relevant doses of chromium-picolinate can harm individual oucomes through DNA damage and extensive alterations in central detoxification / cell-cycle regulating pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Similarly, our findings regarding the stability of chromium picolinate as judged from the level of chromium, demonstrated it to be stable for the whole period of the study in the three dosage forms under the accelerated stability study conditions. This finding agreed with multiple previous studies that showed that chromium-picolinate is a highly stable molecule with an over 95% recovery under forced degradation [68,69].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, our findings regarding the stability of chromium picolinate as judged from the level of chromium, demonstrated it to be stable for the whole period of the study in the three dosage forms under the accelerated stability study conditions. This finding agreed with multiple previous studies that showed that chromium-picolinate is a highly stable molecule with an over 95% recovery under forced degradation [68,69].…”
Section: Discussionsupporting
confidence: 93%
“…The beneficial effect of exercise on the risk of metabolic diseases may be due to the improvement in glucose and insulin sensitivities, inflammatory markers and blood lipids level [ 46 , 47 ]. Exercise combined with micronutrient supplementation such as CrHis and biotin are efficient in preventing or treating various metabolic diseases [ 48 , 49 ]. Chromium (Cr) is an essential trace element particularly involved in carbohydrate, fat, and protein metabolism [ 27 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is the most prevalent form of diabetes worldwide [ 1 , 2 ]. It is characterized by defects in pancreatic insulin secretion or action causing hyperglycemia attributable to disturbances in carbohydrate, fat and lipid metabolism [ 1 ]. The worldwide prevalence of T2DM is increasing and more than 366 million people are expected to be affected by the year 2030 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%